Pandangan Al-Qur’an Terkait Merubah Bentuk Tubuh - Masrury, Farhan (Ta'lim : Jurnal Multidisiplin Ilmu, 2022)
Changing God's creation is one of the phenomena that occurs today due to the influence of technological developments, so that the primitive society will be increasingly eroded by technological sophistication and turn into a modern society that is able to turn ugliness into beauty and disability into perfection. Indeed, Allah forbids humans from changing Allah's creation as described in the Qs. an-Nisa 'verse 119. Mufassirin interprets the conversion in question as changing the nature of God's religion and changing the human body.